A responsabilidade civil pelo risco ambiental Intolerável - DANTAS, Bruno Felipe dos Santos Lacerda (2021)
Under the guise of civil liability, this paper aims to analyze the possibility of configuring collective off-balance sheet environmental damage based on intolerable environmental risk, in accordance with preventive environmental protection. In the face of risk society, the grand ventures have gained prominence in the globalized world for large-scale production. However, people became hostages in their own homes. After all, they have no control over their environment. On the other hand, the historically devastated environment is threatened and jeopardized by risk, if not the classic environmental damage and its severity that destroys families, cities and the entire ecosystem of a given region. This does not exclude the possibility of spreading to other places due to its degree of extension and the lack of necessary containment technique. As will be explained, the principle of full redress promotes formal legal justice as being relatively ineffective, as any attempt at redress or compensation is considered symbolic. Given the problem, the research aimed to clarify the possibility of configuring the risk-damage, new classification adopted by Professor Luciana Chiavoloni in her doctoral dissertation. To this end, the historical evolution, the principles of Environmental Law and its constitutional perspective, fundamental concepts, the configuration of intolerable environmental risk will be analyzed. jurisprudential and doctrinal development on the subject.